Effects of bird predation on canopy arthropods in wandoo Eucalyptus wandoo woodland - Majer, Jonathan; Recher, H. F. (2006)
As top predators, birds may have significant effects on arthropod abundances and affect the trophic structure of arthropod communities through predation of lower order predators (e.g. spiders) and by competition for prey. We investigated the effects of bird predation on canopy arthropods in south-western Australia by using plastic bird mesh to exclude insectivorous birds from the foliage of wandoo Eucalyptus wandoo saplings. Exclosure resulted in an increase in the number of herbivorous and predatory arthropods. Total arthropods (with and without ants), spiders, adult Coleoptera, and larval Lepidoptera were significantly more abundant on meshed than unmeshed saplings. All size-classes of arthropods, taxa grouped, were more abundant on meshed than unmeshed saplings, but with no evidence of a disproportionate increase of the largest arthropods on meshed saplings.